PENERAPAN MODEL STAD BERBANTUAN CANVA PADA FISIKA KELAS XI SMAN 7 PINRANG - Parida; Qaddafi, Muhammad; Anggereni, Santih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This quantitative research aims to analyze the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model assisted by interactive Canva media on the physics learning outcomes of eleventh-grade students at SMAN 7 Pinrang, specifically regarding fluid dynamics. Employing an experimental method with a one-group pretest-posttest design, the study utilized pre- and post-intervention testing as the primary instrument for data collection. The data were subjected to descriptive and inferential statistical analysis to determine the significance of the improvement. The results demonstrate a significant enhancement in students' physics learning outcomes, as evidenced by a substantial increase in mean scores and an N-gain achievement within the moderate-to-high category. This improvement is attributed to the synergistic effect of the STAD model, which fosters collaboration within heterogeneous groups to encourage peer tutoring, and the use of interactive Canva, which clarifies abstract fluid concepts through engaging visual representations. Furthermore, this approach increased student engagement and active participation during the learning process. The study concludes that the STAD model integrated with interactive Canva is a highly effective instructional strategy for improving conceptual understanding and academic performance in physics.